How to influence consumer mindset: A perspective from service recovery. (May 2018) - Harun, Ahasan; Rokonuzzaman, Md; Prybutok, Gayle; Prybutok, Victor R.
Abstract: This research examines a theoretical framework that evaluates the effectiveness of service recovery strategies in influencing post-complaint consumer mindset. Based on the Justice Theory (Adams, 1963 ), this study investigates the interrelationships among the focal constructs related to consumers' behavioral and attitudinal factors after experiencing service failure. We evaluate the proposed framework through the partial least squares structural equation modeling (PLS-SEM). This study contributes to the extant literature by: a) identifying the antecedents of positive word-of-mouth in service recovery context, b) helping service industry practitioners by showing a way to tailor their service recovery strategies through the use of importance-performance map analysis (IPMA) at both the construct and indicator levels, and c) providing a unique platform by analyzing real consumer experiences as opposed to the most extant researches which examine simulated consumer behaviors based on hypothetical scenarios. The results of this study indicate that through effective execution of service recovery strategies, it is possible to create strong sense of justice in a consumer's mind, which then service industry practitioners can leverage through loyalty to create more impact on post-complaint consumer mindset. This study also provides several theoretical and managerial implications.